Mentoring for the Educational Leadership Professoriate: Perspectives From Jay D. Scribner Mentoring Award Recipients and Mentees. (September 2019) - Hackmann, Donald G.; Malin, Joel R.
This article presents findings from a study of Jay D. Scribner Award recipients. The purposes were to learn why professors engage in mentoring and to identify activities and supports provided to mentees. Interviews were held with the 12 recipients and 24 mentees who submitted letters in support of their nominations, with Mertz's conceptual model of mentoring guiding data analysis. Findings revealed mentoring activities were based upon mentees' career stages and institutional contexts, and aligned with Mertz's mentoring continuum. Relationships emerged informally, included individual and group mentoring, were characterized by relational equality, and resulted in long-term research partnerships and friendships.